2019
DOI: 10.1109/tsg.2018.2888581
|View full text |Cite
|
Sign up to set email alerts
|

Non-Intrusive Load Monitoring by Voltage–Current Trajectory Enabled Transfer Learning

Abstract: Non-Intrusive Load Monitoring (NILM) is pivotal in today's energy landscape, offering vital solutions for energy conservation and efficient management. Its growing importance in enhancing energy savings and understanding consumer behavior makes it a pivotal technology for addressing global energy challenges. This paper delivers an in-depth review of NILM, highlighting its critical role in smart homes and smart grids. The significant contributions of this study are threefold: Firstly, it compiles a comprehensiv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
104
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 168 publications
(105 citation statements)
references
References 184 publications
1
104
0
Order By: Relevance
“…In the literature, the voltage-current (V-I) trajectories were found powerful for formulating appliance signature. In [21] and [22], appliances were classified using V-I trajectory converted to grey-scale and color coded image, respectively. Though the models in [21] were able to successfully detect a large number of appliances, the washing machine, fan, fridge and air conditioner were not identified with better score.…”
Section: Related Workmentioning
confidence: 99%
See 2 more Smart Citations
“…In the literature, the voltage-current (V-I) trajectories were found powerful for formulating appliance signature. In [21] and [22], appliances were classified using V-I trajectory converted to grey-scale and color coded image, respectively. Though the models in [21] were able to successfully detect a large number of appliances, the washing machine, fan, fridge and air conditioner were not identified with better score.…”
Section: Related Workmentioning
confidence: 99%
“…Though the models in [21] were able to successfully detect a large number of appliances, the washing machine, fan, fridge and air conditioner were not identified with better score. Reference [22] used AlexNet transfer learning methodology. The authors in [17] used wavelet coefficients for identification of four appliances using Decision Tree (DT) and Nearest Neighbor (NN) classifiers on the setting of semi-supervised learning.…”
Section: Related Workmentioning
confidence: 99%
See 1 more Smart Citation
“…It has been demonstrated that transforming the V-I trajectory into image representation and feeding it as the input to machine learning classifiers improves classification performance [11,14,[17][18][19][20][21]. However, the presented works use single-label learning, thus assuming that only one appliance is active at a time.…”
Section: Introductionmentioning
confidence: 99%
“…To improve the discriminating power of our method, we apply the Fryze power theory, which enables the decomposition of the current waveform into active and non-active components in time-domain [20,28]. Our research hypothesis is that the sum of the active and non-active components will exhibit unique and consistent characteristics based on the appliances that are running simultaneously, hence providing a distinctive feature for multi-label classification.…”
Section: Introductionmentioning
confidence: 99%